Leading in the time of COVID-19 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
From planning well into the future to planning four weeks in advance, Ayala Corporation’s Chairman and CEO adjusted aggressively to navigate an unprecedented crisis.